UPAYA GURU MENINGKATKAN MINAT BACA ANAK USIA 5-6 TAHUN DI MASA PANDEMI COVID- 19 - Wulandari, Ayu; Syukri, M.; Linarsih, Andini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The research on teachers' efforts to increase interest in reading children aged 5-6 years during the COVID-19 pandemic at the Pontianak Integrated Early Childhood Education (PAUD) was motivated by the exposure of UNESCO data which stated that Indonesia ranks second from the bottom in terms of world literacy, meaning that reading interest in Indonesia is very low. According to UNESCO data, the reading interest of the Indonesian people is very concerning, only 0.001%. This study aims to determine the efforts of teachers to increase interest in reading for children aged 5-6 years during the COVID-19 pandemic at the Kartini Integrated PAUD Pontianak. The research method uses descriptive qualitative research methods with the type of case study research. The results of the study in an effort by teachers to increase reading interest in children aged 5-6 years during the covid-19 pandemic at the Kartini Integrated PAUD Pontianak, were carried out using various media, methods and conducting appropriate learning evaluations to increase children's reading interest.